Aplicación de un modelo de acompañamiento docente para la instalación e implementación curricular (MADIIC) Facultad de Medicina de la Universidad de Chile - Figueroa SM., Carolina; Gutiérrez P., Sandra Gutiérrez P. (Revista Hospital Clínico Universidad de Chile, 2014)
Curricular innovation at the University of Chile Faculty of Medicine carries a considerable challenge to teaching practice and to all the “actors” involved in the educational process. It is essential to create the right conditions to perform the desired improvements; therefore, keeping this in mind, from the year 2012 we began to apply a model of Teachers’ Accompaniment, favouring their reflection capabilities through out a collaborative and participatory process for proper installation and implementation of the innovation process.